Distinct HLA-E peptide complexes modify antibody-driven effector functions of adaptive NK cells - Rölle, Alexander; Jäger, Dirk; Momburg, Frank (Cell reports, 2018)
Adaptive NK cells are characterized by profound alterations in multiple signaling molecules, transcription factors, and epigenetic modifications compared with canonical NK cells. Although their existence is associated with prior exposure to human cytomegalovirus (HCMV), key questions regarding their regulation and function remain. A large proportion of adaptive NK cells express the activating receptor CD94/NKG2C, binding to human leukocyte antigen E (HLA-E), that presents a limited set of peptides. We show that adaptive NK cells discriminate differences between HLA-E-peptide complexes with exquisite specificity. Prolonged exposure to an environment displaying the HLA-E peptide ligand VMAPRTLFL, derived from the leader sequence of HLA-G, enriched adaptive NK cells with low FcεRγ expression, upregulated CD25 expression, increased proliferative activity, and resulted in elevated antibody-dependent cellular cytotoxicity and IFN-γ responses compared with other HLA-E peptide complexes. Our study demonstrates that recognition of alterations in the HLA-E ligandome via an activating receptor can influence heterologous effector mechanisms and proliferation in adaptive NK cells.
Gesehen am 16.04.2020